Human monoclonal antibodies protect against viral-mediated pneumococcal superinfection - Gingerich, Aaron; Mahoney, Lauren; McCormick, Anna L.; Miller, Rose J.; Mousa, Jarrod (Frontiers in Immunology, 2024)
Community-acquired pneumonia (CAP) is a significant global health concern. Among CAP cases, 25% are attributed to the bacterium Streptococcus pneumoniae (Spn), which can be exacerbated by primary viral infections. Common viral infections associated with Spn infection include influenza A virus (IAV), respiratory syncytial virus (RSV), and human metapneumovirus (hMPV), as these infections can increase host vulnerability to secondary bacterial infections.Consequently, this can lead to severe complications due to the intertwined interactions between infecting pathogens and the compromised host immune response. Our previous work revealed the protective potential of human monoclonal antibodies (mAbs) that target the conserved pneumococcal histidine triad protein D (PhtD) of Spn. In this study, we investigated the efficacy of an anti-PhtD mAb cocktail therapy to improve survival rates in three distinct viral/bacterial coinfection models: IAV/Spn, hMPV/Spn, and RSV/Spn. The mAb cocktail PhtD3+7 outperformed antiviral mAb treatments in multiple coinfection models, resulting in prolonged survival. In the IAV/Spn model, treating with either anti-viral or anti-bacterial mAbs caused a 2-4 log reduction in bacterial titers within blood and lung samples. In the hMPV/Spn coinfection model, mAb cocktail PhtD3+7 conferred greater protection than the previously documented hMPV neutralizing mAb MPV467. Both mAb treated groups displayed significantly reduced bacterial titers in the blood and lungs, with PhtD3+7 being the most effective. In the RSV/Spn coinfection model, PhtD3+7 provided slightly greater protection than the antiviral mAb D25. Notably, only PhtD3+7 managed to decrease the bacterial titers in the blood and lungs of RSV/Spn coinfected animals. Considering the increasing threat of antibiotic resistance rendering current therapeutic options less effective, these studies highlight important options for combating viral and secondary pneumococcal coinfections.